2019
DOI: 10.3390/catal9090770
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Medium-Chain Structured Phospholipids over Mesoporous Organosulfonic Acid-Functionalized SBA-15 Catalysts

Abstract: It is highly desirable that efficient recoverable heterogeneous catalysts should be developed to replace the costly biocatalysts used in producing structured phospholipids (SPLs) with medium-chain fatty acids (MCFAs). Thus, mesoporous propyl and phenyl sulfonic acid-functionalized SBA-15 materials synthesized via surface modification methods were investigated for the soybean lecithin interesterification with methyl caprate or caprylate. The physicochemical properties of the synthesized solid acids were deeply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Consequently, the M‐SBA‐15 (M = Zn, Al) catalysts with much higher quantities of strong Lewis acid sites are more effective for MCP production compared with the SBA‐15 parent, which is supported by the pyridine–FTIR results as illustrated in Fig. 1 and a recent publication 33 . Another fact is that the mesostructures of SBA‐15‐type catalysts could better facilitate the acidolysis processes than the homogeneous ones as discussed in Figs 2 and 3.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Consequently, the M‐SBA‐15 (M = Zn, Al) catalysts with much higher quantities of strong Lewis acid sites are more effective for MCP production compared with the SBA‐15 parent, which is supported by the pyridine–FTIR results as illustrated in Fig. 1 and a recent publication 33 . Another fact is that the mesostructures of SBA‐15‐type catalysts could better facilitate the acidolysis processes than the homogeneous ones as discussed in Figs 2 and 3.…”
Section: Resultssupporting
confidence: 57%
“…When the temperature was eventually raised to 70 °C, C10:0 and C8:0 incorporation reduced dramatically to ~27.57 ± 0.42% (or 21.38 ± 0.27%) and ~24.12 ± 0.29% (or 20.39 ± 0.09%), respectively. According to these results, it is indicated that parts of the MCP products are unstable at higher reaction temperature, resulting in their decomposition reaction and further formation of by‐products, as reported in the literature 33 . Therefore, the desired MCFA‐enriched SPLs should be synthesized at 50 °C for 6 h with 1:9 substrate mass ratio and 5 wt% catalyst loading.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Thereafter, the thus-synthesized Zn-SBA-15 material was functionalized with phenyl sulfonic acid groups according to the procedures reported in the literature. 29 Initially, trimethoxyphenylsilane (3.0 g) was added dropwise into a mixture of Zn-SBA-15 (1.0 g) and toluene (20 mL). The attained suspension was then refluxed for 24 h under a N 2 atmosphere.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%